건설플랜트산업에서 Digital Transformation이 프로젝트 성과에 미치는 영향 연구 - 최창영; 강신봉; Chang Yeong Choi; Sinbong Kang (한국건설관리학회 논문집, 26(4), 2025)
In this study, a new research model and hypothesis were proposed to systematically introduce digital transformation (DX, DT, hereinafter referred to as "DX") to domestic plant construction industry, which has been struggling with management due to recent weakening price competitiveness, lack of project management capabilities, and lack of technology and innovation. In the research model setup, digital competency was set as the independent variable, digital maturity as the mediator variable, and CEO's willingness to utilize DX and client's demand intensity to utilize DX as the moderator variables, allowing for the verification of project performance as the dependent variable. The survey is meaningful as an empirical study because it targets samples with experience in the plant industry and DX. As a result of this study, it was verified that the introduction of DX into plant construction industry has a significant impact on project performance and is a strategic tool that can bring about innovative changes in business. 본 연구에서는 최근 가격경쟁력 약화, 프로젝트관리 역량 부족, 기술력 정체와 혁신 부족으로 경영에 어려움을 겪고 있는 국내 플랜트건설산업에 디지털전환(Digital Transformation, DX, DT, 이하 "DX"로 표기함)을 체계적으로 도입하여 재도약을 위한 방향을 제시하기 위해 새로운 연구모형 및 가설을 제시하였다. 연구모형 설정에서는 디지털역량을 독립변수로, 디지털 성숙도를 매개변수로, 최고경영자의 DX 활용 의지와 발주처의 DX 활용 요구 강도를 조절변수로 설정하여 종속변수인 프로젝트 성과를 검증할 수 있게 하였다. 설문은 플랜트산업 분야와 디지털전환의 경험이 있는 표본을 대상으로 하였기 때문에 실증연구로서 의미가 있다. 본 연구 결과, 플랜트건설산업에 디지털전환의 도입은 프로젝트 성과에 큰 영향을 미치며, 비즈니스에 혁신적 변화를 가져올 수 있는 전략적 도구라는 것을 검증하였다.